PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MODEL PEMBELAJARAN PAIKEM TERHADAP PENGETAHUAN DAN KETERAMPILAN ORAL HYGIENE PADA ANAK USIA PRASEKOLAH DI RA TARBIYATUS SHIBYAN DESA GUYANGAN - Siti Nur Afifah; Dodik Hartono; Iin Aini Isnawati (JOURNAL SAINS STUDENT RESEARCH, 2025)
Preschool-aged children are a vulnerable group susceptible to oral health problems; therefore, they need to be equipped with oral hygiene knowledge and skills to support healthy oral habits. This study aimed to determine the effect of health education using the PAIKEM learning model on children's oral hygiene knowledge and skills.Design in this research is a pre-experimental design with a one-group pre- post-test approach. The population comprised 32 respondents, with all 32 included in the study using total sampling. The intervention was implemented over eight consecutive days, for 30 minutes each day, using questionnaires and Standard Operating Procedures (SOP) as measuring instruments. Data were analyzed using the Wilcoxon test.The results showed improvements in oral hygiene knowledge and skills from pre-test to post-test. The pre-test revealed that the majority (24 respondents, 75%) were in the "poor" knowledge category. The post-test showed that the majority (23 respondents, 71.85%) were in the "good" knowledge category. For skills, the pre-test indicated that the majority (22 respondents, 68.8%) were in the "low" skill category, while the post-test showed that the majority (8 respondents, 25%) were in the "moderate" skill category. The Wilcoxon test yielded a p-value of 0.000 (<0.05), indicating a significant effect of health education using the PAIKEM model on the oral hygiene knowledge and skills of preschool children at RA Tarbiyatus Shibyan, Guyangan.Health education using the PAIKEM model can foster innovation and creativity in children, making oral hygiene education more effective in reducing the risk of oral diseases.